Actual and intended growth in family firms and non-family-owned firms: are they different?. Issue 1 (5th December 2017) - Saridakis, George; Lai, Yanqing; Muñoz Torres, Rebeca I.; Mohammed, Anne-Marie
Abstract : Purpose: Drawing on the motivation theory and family business literature, the purpose of this paper is to investigate the influence of family effect in growth behaviour of small-and-medium-sized enterprises (SMEs) in the UK. Design/methodology/approach: The authors first compare the actual and expected growth of family and non-family-owned SMEs. The authors then compare the growth behaviour of small family firms managed by owner-directors and small family businesses co-managed by family and non-family directors with the non-family-owned SMEs. Findings: The authors find a negative effect of family ownership on actual and intended small business growth behaviours. In addition, the findings also suggest that small family firms co-managed by non-family and family directors are no different from non-family-owned firms, in terms of reporting past actual growth in employment size and turnover as well as expecting growth in workforce size and turnover. The authors also observe a significant difference in anticipating sales growth between family-controlled and non-family-controlled firms. However, this difference is not explained by the heterogeneity of a top management team. Practical implications: The study has important implications for managerial practice to family firms and on policies that improve the growth of SMEs. Specifically, the competence of managers and decision makers matters considerably in evaluating the efficient operation of the business and maximising the economic growth in SMEs. Originality/value: The study makes two important theoretical contributions to small business growth literature. First, the findings underline a negative family effect in the actual and expected growth behaviour of SMEs. Second, the mode of family ownership alone may not sufficiently capture family effect and offer a thorough understanding of growth behaviour in SMEs.